La Gestión Financiera del Gobierno Autónomo del cantón Riobamba y su incidencia de la cartera vencida en el presupuesto periodo 2022. - Amores Castillo, Bianca Teresa (2023)
This research project is addressed to the Financial Management of the Autonomous Government of the Riobamba city and its Incidence of the overdue portfolio in the 2022 period budget, it is intended that through financial management reduce the percentage of overdue portfolio, through the recovery of it and in turn the impact it has on the budget. This research is supported by documented bibliographical methodology and field research, using research techniques such as: observation since the current situation is verified, data collection through trades to receive information from the institution, interviews with officials who have under responsible for the non-performing portfolio area by means of a questionnaire as an instrument, a survey of all officials of the financial department and sub-processes. Based on the information obtained, the factors that cause the increase in the overdue portfolio, the degree of affectation that it generates in budget planning and the shortcomings in financial management were determined.